Pergeseran Makna Kesenian Musik Bordah Pada Upacara Perkawinan Masyarakat Melayu di Kelurahan Gunting Saga - Situmorang, Syaraya Hartika; Sebayang, Vanesia Amelia; Suroso, Panji (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Bordah music is a cultural heritage of the Malay community that is full of spiritual and religious values. However, in the context of marriage ceremonies in Gunting Saga Village, this art has experienced a shift in meaning due to the influence of modernization and social change. This study aims to: (1) describe the form of presentation of Bordah art in the wedding ceremony of the Malay community; (2) analyze the factors causing the shift in the meaning of Bordah; and (3) examine the community's perception of changes in the form and function of the art. This research uses a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Data analysis was conducted inductively-qualitatively with a semiotic approach to reveal the symbolic meaning contained in Bordah performances. The results showed that Bordah art has shifted from a sacred-religious function to a symbolic entertainment function. This shift is influenced by the modernization of musical instruments, the decline in the regeneration of artists, and changes in the cultural preferences of the younger generation. This research contributes to the study of traditional cultural adaptation to modernization, and offers a theoretical understanding of the transformation of meaning in local performing arts practices. The implications of these findings suggest the need for cultural preservation strategies that are responsive to social and generational dynamics.